1996
DOI: 10.1038/nm0896-918
|View full text |Cite|
|
Sign up to set email alerts
|

The seroepidemiology of human herpesvirus 8 (Kaposi's sarcoma–associated herpesvirus): Distribution of infection in KS risk groups and evidence for sexual transmission

Abstract: Striking differences in Kaposi's sarcoma (KS) risk for AIDS patients who acquire HIV via homosexual activity and those whose HIV infections derive from blood product exposure suggest the presence of a sexually transmitted agent other than HIV in the development of KS. Using an immunofluorescence assay, we examined serum samples from 913 patients for the presence of antibody specific for infection by human herpesvirus 8 (HHV8), an agent whose genome is regularly found in KS tissue. The distribution of HHV8 sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
407
3
21

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(471 citation statements)
references
References 25 publications
40
407
3
21
Order By: Relevance
“…We used sera from patients with KS for a positive control, and all of these sera were positive for HHV-8 IgG antibody. The prevalence of HHV-8 in 5.2% of blood donors in the USA correlates with that previously reported using both latent IFA and immunoblot assays (Gao et al, 1996a;Kedes et al, 1996;Miller et al, 1996). The higher prevalence of HHV-8 in adults from Uganda (38.7%) and Zambia (37.5%) correlates with the incidence of endemic KS and the high incidence of AIDS-associated KS in these countries (Wabinga et al, 1993).…”
Section: Age and Sex Of Donorssupporting
confidence: 84%
“…We used sera from patients with KS for a positive control, and all of these sera were positive for HHV-8 IgG antibody. The prevalence of HHV-8 in 5.2% of blood donors in the USA correlates with that previously reported using both latent IFA and immunoblot assays (Gao et al, 1996a;Kedes et al, 1996;Miller et al, 1996). The higher prevalence of HHV-8 in adults from Uganda (38.7%) and Zambia (37.5%) correlates with the incidence of endemic KS and the high incidence of AIDS-associated KS in these countries (Wabinga et al, 1993).…”
Section: Age and Sex Of Donorssupporting
confidence: 84%
“…During latent infection only a small subset of genes important for maintaining viral latency by modulating various cellular pathways are expressed (3,14,24,25,51,60). Latency-associated nuclear antigen is one of the prominent proteins detected in all forms of latency and shown to be critical for maintenance of latency (1,9,17,25,43).…”
Section: Discussionmentioning
confidence: 99%
“…This finding, coupled with the higher prevalence of OtHV-1 in the genital tract, led the authors to suggest that the virus is sexually transmitted and that there was similarity between the epidemiology of OtHV-1 infection in CSL and HHV-8 in humans [61]. Studies into the epidemiology of HHV-8 have suggested that sexual activity plays an important role in the transmission of the virus [62], particularly in the case of AIDS-associated Kaposi's sarcoma [63,64].…”
Section: (D) Infectious Diseasementioning
confidence: 99%